2007
DOI: 10.1007/s11665-007-9080-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Magnetic Properties of Calcium-Substituted Li-Zn Ferrite

Abstract: The effect of Ca-substitution on the physical and magnetic properties of Li 0.3-0.5x Zn 0.4 Ca x Fe 2.3-0.5x O 4 ferrites (x = 0.0, 0.01, 0.02, 0.03, and 0.05), prepared by the standard ceramic method, has been studied. It is found that the saturation magnetization increases up to x = 0.01 and then it decreases. On the other hand, the initial permeability decreased while the Curie temperature remained almost constant with increasing x. The coercivity and remanence ratio increased with increasing x.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…about the preparation conditions were previously reported [8,9]. X-ray diffraction patterns were performed using a diffractometer of type X'Pert Graphics and identified with Cu K␣ radiation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…about the preparation conditions were previously reported [8,9]. X-ray diffraction patterns were performed using a diffractometer of type X'Pert Graphics and identified with Cu K␣ radiation.…”
Section: Methodsmentioning
confidence: 99%
“…The porosity percentage P(%), the initial permeability i , the coercivity Hc, the remanence Br and the dc electrical resistivity were all measured according to the techniques mentioned in Ref. [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their superior properties (such as low cost, favorable magneto-dielectric, and high Curie temperature), Li and substituted lithium ferrites were investigated for microwave and electronic applications [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the modification of these properties has been investigated by various authors through the substitution of Liferrite, prepared by ceramic method (conventional method) with different ions of different concentration [3][4][5][6]. Fu reported that, the preparation of Li-ferrites by non-conventional method (microwave induced combustion) have lead to decrease the saturation magnetization and the Curie temperature with increasing chromium content, Cr [7].…”
Section: Introductionmentioning
confidence: 99%